Risk assessment of multiple mycotoxins in infant food consumed by Portuguese children – the contribute of the MYCOMIX project - Alvito, Paula (2015)
Abstract publicado em: Toxicology Letters. 2015; 238 (2, Suppl.): S117. doi:10.1016/j.toxlet.2015.08.377. Disponível em: http://www.sciencedirect.com/science/article/pii/S0378427415023164